Estudo da degradação do cloridrato de fluoxetina por peróxido de hidrogênio e composto contendo prata coloidal - Joroski, Vinicius Tiago (2017)
Every year, thousands of tons of drugs are disposed of worldwide in the form of domestic, industrial and hospital effluents, not only due to inadequate waste disposal, but also due to the presence of these drugs in the excretion of users of the products. Through several studies, it has been demonstrated the impact that low concentrations of these drugs in the environment can cause to the organisms, besides the aquatic bodies. Among the drugs widely used in the world for the treatment of psychic diseases, fluoxetine is the one that has the most representativeness, and its presence is evident in the environment. As verified in the existing literature, concentrations of this drug could be found in innumerable cases when analyzing natural, surface and underground waters and, in the concentrations found, cause changes in aquatic life. Therefore, in order to avoid impacts on living organisms, it is pointed out that forms of treatment for these wastes should be developed in order to mitigate the problem. The present study aims to study the behavior of fluoxetine in water, evaluated by reading in a UV-vis spectrophotometer at a concentration of 40 mg.L-1 , exposed to different pH ranges and different degradation processes performed in a GERMETC reactor, with 5W UV lamp, at 3 hours exposure time. Fluoxetine solutions were exposed to combinations of hydrogen peroxide at 60 mg.L-1 , colloidal silver at 0.64 mg.L-1 and UV radiation and samples were read on the UV-vis spectrophotometer at minor intervals during 3 hours of exposure, allowing analysis of the evolution of degradation. The samples exposed to the various treatments were submitted to toxicological tests according to ABNT NBR 12713/2016 (Aquatic Ecotoxicology - Acute Toxicology – Daphnias magna. Test Method) to obtain the FTD values of the resulting solution. It was observed that there was degradation of fluoxetine when exposed to UV radiation (22% reduction), indicating activity when exposed to UV, and degradation value of 23% when exposed to UV in the presence of colloidal silver. When not exposed to UV radiation, no significant reaction of the drug was observed in the presence of hydrogen peroxide, in the presence of silver or the combination of the two. When UV radiation and hydrogen peroxide were applied, the concentration reduction reached 94% and, with the application of radiation with hydrogen peroxide and colloidal silver, the reduction was 92%. The FTD of 32 was found for 1) fluoxetine at study concentration; 2) for a sample that was stored for 5 months and 3) a sample exposed to hydrogen peroxide without UV radiation. All other assays resulted in an increase in FTD toxicity of 128, except for the sample exposed to hydrogen peroxide, colloidal silver and UV radiation whose FTD was 64. It was found that, through this experiment, even though there was degradation of the drug, there is formation of intermediate compounds that can be monitored with the help of a spectrophotometer and, in addition, these compounds can present a greater toxicity to the isolated substance. As future works, it is possible to carry out the application in the study of different concentrations and longer exposure times, as well as other Advanced Oxidative Processes (AOPs).